A Japanese patient with a VCP mutation c.290G > A (p.G97E) presenting a rapid progressive respiratory failure. Issue 6 (3rd October 2019) - Nomura, Emi; Ohta, Yasuyuki; Sato, Kota; Kawahara, Yuko; Takemoto, Mami; Takahashi, Yoshiaki; Matsumoto, Namiko; Yunoki, Taijun; Yamashita, Toru; Hishikawa, Nozomi; Nishino, Ichizo; Abe, Koji
Abstract: Inclusion body myopathy with Paget's disease of bone and frontotemporal dementia (IBMPFD) is an autosomal dominant disorder caused by mutations in the valosin‐containing protein ( VCP ) gene. IBMPFD usually presents progressive limb muscle weakness resulting in wheelchaired after mean course of 9 years with myopathy, and Paget's osteolytic lesions and frontotemporal dementia (FTD) rarely present respiratory failure. Different from previous reports, we reported a Japanese IBMPFD patient with a VCP mutation c.290G > A (p.G97E), presenting a progressive respiratory failure accompanied by wheelchaired in only 6 years after myopathy onset, suggesting unique relationship between clinical severity and c.290G > A (p.G97E) mutation of VCP gene in Japanese.